2015
DOI: 10.1007/s40195-015-0306-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dislocation Boundary Structure in Al–Li Alloy During Bending

Abstract: The dislocation boundary structures of 2060-T8 alloy during bending were investigated by backscattered electron imaging, electron backscattered diffraction, and misorientation axes maps. Experimental result shows that typical dislocation boundary structures, which depend on grains' orientation, are formed in grains during bending. The microstructure of type A is mainly observed in grains near brass, copper, and Goss orientations; microstructure of type B is mainly found in grains near S orientation; microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Besides, the cost of Al-Li alloys is higher than that of traditional Al alloys because of the ageing conditions and comparable strength. Therefore, various studies have been carried out to investigate metal forming technologies (i.e., hydroforming, impact hydroforming, stamping, bending, and superplastic forming) under different working conditions (i.e., cold, warm, and hot deformation) to identify an alternative manufacturing route and to optimize the working conditions to decrease the higher costs related to the addition of Li and the manufacturing of sound, complex shape components from Al-Li alloys [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the cost of Al-Li alloys is higher than that of traditional Al alloys because of the ageing conditions and comparable strength. Therefore, various studies have been carried out to investigate metal forming technologies (i.e., hydroforming, impact hydroforming, stamping, bending, and superplastic forming) under different working conditions (i.e., cold, warm, and hot deformation) to identify an alternative manufacturing route and to optimize the working conditions to decrease the higher costs related to the addition of Li and the manufacturing of sound, complex shape components from Al-Li alloys [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] .…”
Section: Introductionmentioning
confidence: 99%
“…In Fig.7(c), the band structure can be observed obviously, the traces are analyzed to be parallel to the {111} slip plane, it can be speculated that the band structure is GNBs structure. The results of the present study show that this band structure is related to the grain's orientation and strain [25]. The extended planar boundaries are termed GNB as they are believed to accommodate systematic slip differences in the grain.…”
Section: Resultsmentioning
confidence: 65%
“…Thus, mechanical strength was increased with reduced bending radius. Subsequently, Jin et al [10] investigated the dislocation boundary structures of AA2060 during the bending process and found that three types of microstructures were formed. Later, Jin et al [11] analysed the damage mechanisms and the microstructure evolution of AA2060-T8 during bending using in-situ bending test.…”
Section: Introductionmentioning
confidence: 99%